Youth Research under the Microscope: A Conceptual Analysis of Youth Information Interaction Studies. Issue 1 (13th October 2021) - Figueiredo, Vanessa; Meyers, Eric M.
Abstract: Youth information interaction (YII) research has focused on challenges youth encounter when interacting with information across different contexts. Although these studies have been fundamental to outline youth information behaviour, the absence of YII theoretical frameworks might limit our approach to contemporary issues, such as the increased use of apps and mobile devices for information searching. This paper presents a conceptual analysis of studies conducted between 1997–2020 to explore predominant epistemological stances and cognitive frameworks in YII. The conceptual analysis generated five typologies operationalizing YII studies in seven categories: epistemological stance, knowledge assumption, cognitive framework, study type, study design, theoretical framework, study outcomes, and applications. The findings suggest that YII research have converged to empiricist and rationalist stances supporting exploratory approaches. These findings elicit the urgency for the development of theoretical frameworks that support the validity of YII phenomena with the purpose of developing a new agenda for YII research.